The oil palm stakeholders perception towards participation factors for cattle integration system - Lim, Hock Chai (2019)
First quarter of the year 2018 recorded 32.4 million population in Malaysia, and projection done by Department of Statistic Malaysia (DoSM) expected a total of 41.5 million population by the year 2040. With such a huge population, food security has become one of the important issues that needs to be sorted out and organized carefully. Agriculture sector is found to contribute not only towards National Gross Domestic Product (GDP), but it also contributes in ensuring food security. For our country to keep moving towards high income nation by the year 2020, the economy has to increase steadily in tandem with the per capita income of our nation. Meat demand has also increased from time to time and through the National Key Economic Area (NKEA), 300,000 cattle are targeted to be reared through integration system in oil palm plantation. With the stocking rate of two (2) cattles per hectare, ideally, we do not need to import meat from other countries anymore. However, in reality, our country is still unable to cope with the meat demand. This study was conducted in order to get better understanding of stakeholders’ perception on inclination and repulsion factors towards implementing cattle integration in their oil palm plantation. The study involved 274 respondents who are involved in oil palm plantation industry and cattle husbandry all over the country. Six (6) inclination factors and eight (8) repulsion factors were found to influence the stakeholders’ perception. Binomial logistic regression was conducted towards all the factors involved in determining the most influential factor that contribute to stakeholders’ intention in implementation of cattle-oil palm integration system. Three (3) independent variables were found to be the most influential factors in stakeholders’ decision in implementing cattle-oil palm integration system which are the stakeholders’ inclination interest factor, inclination economic factor and the stakeholders’ repulsion interest factor. The results of the study can be further debated and discussed in order to draft solid and viable guideline and policy on integrated farming as well as increasing meat production in our country.